Structural, metamorphic and geochronological studies in the south-east Tauern (Austria) - Waters, D (1976)
An area of c. 50 km2 within the Altkristallin Sheet (Upper East Alpine Sheet sensu lato) south of the Tauern Window has been mapped at a scale of 1:10,000. The rocks have been tilted southwards by uplift of the Hohe Tauern area, and the mapped area represents a section from deep tectonic levels characterised by early Alpine (80 my) K-Ar mineral ages, through to higher levels with Hercynian (220-300 My) ages. The rocks are mainly metasediments with minor amounts of metamorphosed igneous material. Three principal schist types are distinguished. in the south: phyllitic garnet-muscovite and quartzose schists. (Kreuzeck Schists). in the north: medium- to coarse-grained mica-schists and para-gneisses (Polinik Schists). in a central zone: schists intermediate in character between the above (intermediate Schists). The tectonic sequence in the map area has been determined by structural analysis and correlation, and the K-Ar mineral age provinces correlated with episodes of mineral growth. The area underwent a major Hercynian deformation and metamorphic event (F1 and M1) of amphibolite facies, with pelitic assemblages dominated by muscovite and garnet, now preserved in the Kreuzeck Schists. Mineral textures indicate syntectonic growth. Relict eclogites in the Polinik Schists are also assigned to this phase. An F2 deformation increases northwards (i.e. downwards in the Altkristallin Sheet) in both intensity and ductile nature. F2 structure has been synthesised across the map area largely by minor fold correlation. Early Alpine metamorphic recrystallisation also increases downwards, obliterating M1 textures and defining a new foliation, axial-planar to F2 folds. Although mineral growth is post-tectonic, it is suggested that M2 and F2 are part of the same tectonic event. An F3 deformation, involving microfolding, flexuring and local chevron-folding, was followed by late Alpine retrogression (M3) which is patchily distributed over most of the area, but more uniformly developed in greenschist facies in the basal kilometer of the Altkristallin Sheet. The Altkristallin Sheet is broken up into blocks by shear zones of (at least) two generations, distinguished on lithological grounds. Strain in quartz fabrics is related to late structures, probably to late arching of the Altkristallin Sheet (F4), and locally to the development of shear zones. Petrograhic mapping revealed the progressive overprint of M1 by M2 assemblages in the Kreuzeck and Intermediate Schists, with the following features in approximate order of appearance, south to north: growth of biotite and plagioclase porphyroblasts gradual increase in muscovite fabric recrystallisation growth of staurolite and breakdown of old garnet breakdown of M2 staurolite and growth of Al-silicates (sillimanite, andalusite and kyanite) Three isograds may be constructed in the Intermediate Schists: an isograd marking the first appearance of M2 staurolite. an andalusite-sillimanite isograd a garnet-Al silicate-biotite isograd Isograds (ii) and (iii) have been mapped over an outcrop length of 8 km and a vertical relief of c. 1 km, and are approximately parallel to the M2 regional foliation and the compositional banding. The Polinik schists lie within the stability field of staurolite + quartz, but entirely within the kyanite field, indicating that there are two distinct areas of differing thermal gradient during M2. Evidence for the conditions of M2 metamorphism is drawn from: experimentally determined equilibria in pelitic compositions the Na content of muscovites calcite-dolomite geothermometry at a locality in the Polinik schists, the pressure-sensitive equilibrium 3 anorthite = grossular + 2 kyanite + quartz equilibria in the iron pelite system K2O-FeO-(MgO)-Al2O-SiO2-H2O, recalculated with self-consistent thermochemical data. The Richardson et al. (1969) Al-silicate triple point is preferred, on the basis of field evidence and (iv) and (v) above. The metamorphic conditions indicated are: for the Polinik schists: 640 ± 25°C at 6 ± 1 kb pressure for the andalusite-sillimanite and garnet-Al silicate-biotite isograds of the Intermediate Schists: 640 ± 20°C at 5 ± 1 kb. In the higher-grade areas there is evidence for a free fluid phase, whose composition was locally buffered by maximum phase pelitic assemblages in the Polinik schists, but was not controlled in the Intermediate Schists. 45 new K-Ar mineral ages are presented from the southern Glockner Group and Kreuzeck Group. Anomalous K-Ar ages, which do not fit the three-phase cooling model, may be qualitatively understood if it is assumed: that in certain circumstances the rate of escape of argon from whole rock systems, on a scale of metres or larger, may be slow compared with escape from millimetre-scale mineral systems. that rapid diffusion in whole rock systems requires the presence of abundant fluids, and that assumption (i) is applicable to fluid-deficient rocks. Corollaries of this approach, which may be tested with evidence from the study area, are: that redistribution of argon will occur between minerals which are open to diffusion within a larger rock system which is closed, or partly closed. that growth of new minerals in a partly closed whole rock system leads to occlusion of argon, yielding an apparent age greater than the true age. that the closure of mineral systems in rock systems which were partially open may allow the recognition of "fossilised" concentration gradients of argon out of bodies of fluid-deficient rock. Anomalous ages due to excess argon in the base of the Altkristallin Sheet and in the M2 staurolite zone of the Intermediate Schists are believed to be caused by the relative concentration of argon due to the removal of H2O and other components of the metamorphic fluid phase by retrograde reactions. The recognition of a high temperature, relatively low pressure metamorphic event, distributed in an elongate east-west trending belt in the Altkristallin, suggests that the two contrasted early Alpine metamorphisms in the Alps constitute paired metamorphic belts indicating southward subduction under the Altkristallin during the Cretaceous. The absence of large volumes of igneous rocks may be explained if the subduction was relatively short-lived. The original base of the Altkristallin (below about 22 km depth) together with the lower lithosphere, was removed before or during the overthrusting of the East Alpine over the Pennine units. Detachment was probably assisted by thermal softening of the lower regions during early Alpine metamorphism.